Pelaksanaan Tahfidz Alquran di Sekolah Menengah Pertama Islam Terpadu - Ramadhany, Nur Fadilah; Muliati, Indah (Prodi Pendidikan Keagamaan Islam, 2024)
The Tahfidz program is one of the programs that aims to get closer to Allah SWT with the hope that memorizing the Quran can increase faith in Allah SWT because of studying, memorizing, and understanding the verses of Allah. Many Quran memorization programs have sprung up in Indonesian schools, one of which is at SMPS IT Kautsar Ilmi which incorporates Quran memorization into the curriculum and subjects that present various interesting programs to minimize the level of boredom of students. This study aims to determine the implementation of Quran memorization at SMPS IT Kautsar Ilmi. The research method used is qualitative with a phenomenological approach. Data collection techniques with observation, interviews, and documentation. The results of the research found that the Tahfidz program successfully achieved the target supported by the programs in it such as Tahsin, Fahmul Quran, Dauroh Quran, Tahfidz Quran, Quran Acceleration, Tahfidz Camp and Leadership Camp.